Fundamentals of typography - Ambrose, Gavin; Harris, Paul, 1971- (Lausanne ; Worthing : AVA Academia, 2006)
Offering an incisive insight into the realization of typographic practice, this title presents a comprehensive introduction to the history of typography, typographic detailing in practice and font generation for print and web
Keywords: Graphic design (Typography); Printing